DRAMATURGI PROFESI SALES PROMOTION GIRL (SPG) DI TOKO ANUGRAH KOSMETIK METROPOLITAN CITY PEKANBARU - Hanesti Asih; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This research had done on Sales Promotion Girl (SPG) in Anugrah’s Cosmetic Shop with inform the life of SPG who worked at shop and the background of SPG’s activity that out of their job. This study used descriptive qualitative research approach with purposive sampling technique as a data collection. The subjects of the research were five SPG. Data collections were collected through in-depth interviews, observation, and documentation. The results of this study indicate that the Dramaturgy of SPG’s at Anugrah MTC Pekanbaru can be seen from the SPG lifestyle that is carried out so that the goals are achieved and performences through SPG performences as a form of embodiment of each of these beauty brands so that the goals are also achieved. And outside of their work as SPG, they show their true selves that many people do not know about it. Where the SPG lifestyle is family oriented and their different appereances is not using makeup dan using products ouside of the their brand when at home. SPG’s front stage can be seen from their lifestyle and appearance when working. However, for back stage life can be known from the discussion of lifestyle and appearance outside of work as SPG. Keywords: Front Stage, Back Stage, Sales Promotion Girl (SPG).